2019
DOI: 10.22456/1679-9216.97156
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection of Bovine Coronavirus N Protein with TaqMan Probe qRT-PCR

Abstract: Background:  Bovine Coronavirus (BCoV) can cause acute diarrhea in newborn calves and adult cattle. BCoV infection may cause losses to production by reduced weight gain, reduced milk yield. Several methods have been applied to detect and diagnose BCoV. However, each assay has its deficiency. Currently, real-time quantitative PCR (qRT-PCR) has been utilized to identify and quantify many viral pathogens since it is a highly sensitive. However, the technical assay varies due to normalization control of the signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…The outcomes demonstrated that the sensitivity and specificity of established triplex probes qRT-PCR were higher than those of universal PCR. These findings were in agreement with previous reports (Geng et al 2019, Gong et al 2020. The established triplex probes qRT-PCR could be applied to early detection and diagnoses of BPV, BCoV and BPIV infections in dairy farms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The outcomes demonstrated that the sensitivity and specificity of established triplex probes qRT-PCR were higher than those of universal PCR. These findings were in agreement with previous reports (Geng et al 2019, Gong et al 2020. The established triplex probes qRT-PCR could be applied to early detection and diagnoses of BPV, BCoV and BPIV infections in dairy farms.…”
Section: Discussionsupporting
confidence: 93%
“…Then, BL-21 competent cells were transferred with the recombinant plasmids of DNA/PCR products and pMD18-T at 37°C overnight. Detail methods were referred to earlier studies on these viruses by our team (Geng et al 2019, Liang et al 2019, Gong et al 2020.…”
Section: Construction Of Recombinant Standard Plasmids Of Pmd18-t-bpv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Os sintomas clínicos podem variar de gravidade e envolve principalmente tosse, febre de remessa, perda de apetite, traqueíte, descarga nasal serosa a mucopurulenta, diarreia e está altamente relacionado com pneumonia em bezerros jovens, com duração de uma a duas semanas. A redução no ganho de peso está altamente relacionado a esta síndrome, afetando desempenho, produção e saúde do mesmo (Saif, 2010;Geng et al, 2019).…”
Section: Síndrome Respiratóriaunclassified
“…Current diagnostic method involves sampling feces and intestinal contents and performing reverse transcription-polymerase chain reactions (RT-PCR) to assess for BCoV [ 7 , 8 , 9 ]. There are vaccines on the market for NCD and specifically BCoV, however, they are typically presented to pregnant cows rather than the calves [ 10 , 11 , 12 ]. Due to the difficulty in establishing a marker for targeted treatment of BCoV infections, recent developments within the field of transcription therapy might enable better diagnostic methods and finely targeted treatments.…”
Section: Introductionmentioning
confidence: 99%